A STUDY IN TO THE DISEASE SEVERITY AND THE CLINICO-RADIOLOGICAL FINDING IN COVID-19 CASES - SINGH, RAVENDRA; JAIN, SWAPNIL; DIWAN, SHISH; SARRAF, SHIVMOHAN; JULKA, ARTI (International Journal of Current Pharmaceutical Research, 2023)
Objective: To study the disease severity and the clinical-radiological finding in COVID-19 patients. Methods: The study was carried out in the Department of Respiratory Medicine of R. D. Gardi Medical College, a tertiary care centre as well a Dedicated Covid Centre in the Ujjain district of MP. Results: A total of 107 patients with COVID-19 disease were assessed; the patients had a median age of 52 y and a mean age of 50.79±16.81 y. The most common clinical presentation were fever which was seen in 80(74.8%) cases, breathlessness (SOB) in 84(78.5%), cough in 71(66.4%), weakness in 29(27.1%), loss of smell in 34(31.8%) and loss of taste in 32(29.9%). The most common co-morbidity present in the study group was diabetes mellitus, which was present in 51(47.7%) cases. The chest radiograph of the patients revealed consolidation in 51(47.7%), GGOs in 29(27.1%), GGO with consolidation in 3(2.8%), reticular pattern in one case and 23(21.5%) cases had the normal pattern. Severity of disease was significantly associated with age of the patient. The typical findings of chest CT in the case of COVID-19 pneumonia include “bilateral, peripheral, and basal predominant ground-glass opacities with or without consolidation and broncho-vascular thickening, In addition, atypical findings are “cavitations, central upper lobe predominance, nodules, masses, tree-in bud sign, and lymphadenopathy A significant statistical correlation was found between CT severity score. Conclusion: The radiology played a very important part in the diagnosis and management of covid patients during the pandemic. The typical presentation of chest radiographs and HRCT thorax helped in diagnosing cases even when the RTPCR, RAT were negative or not available and chest CT severity score of patients positively correlated with clinical severity, inflammatory laboratory markers, especially the CRP, LDH, D-dimer and S. Ferritin and hence was very useful as an predictor of disease severity.